Marine collagen/apatite composite scaffolds envisaging hard tissue applications - Diogo, G. S. (2018)
The high prevalence of bone defects has become a worldwide problem. Despite the significant amount of research on the subject, the available therapeutic solutions lack efficiency.Â  Autografts, the most common used approaches to treat bone defects have limitations such as donor site morbidity, pain and lack of donor site. Marine resources emerge as an attractive alternative to extract bioactive compounds for further use in bone tissue engineering approaches. On one hand they can be isolated from by-products, at low costs, creating value from products that are considered waste for the fish transformation industry. One the other hand, religious constraints will be avoided. We isolated two marine origin materials, collagen from shark skin (Prionace glauca) and calcium phosphates from teeth of two different shark species (Prionace glauca and Isurus oxyrinchus), and further proposed to mix them to produce 3D composite structures for hard tissue applications. Two crosslinking agents, EDC/NHS and HMDI, were tested to enhance scaffoldsâ properties, with EDC/NHS resulting in better properties. The characterization of the structures showed that the developed composites could support attachment and proliferation of osteoblast-like cells. A promising scaffold for the engineering of bone tissue is thus proposed, based on a strategy of marine by-products valorisation.